Implementasi HOTS Pada Pembelajaran PAI melalui Kegiatan P5 dalam Meningkatkan Kemampuan Problem Solving Siswa - Fitroni, Achmad Ma’ruf; Hamidah, Tutik; Sudirman, Sudirman; Ma’ruf, Rachmad Arif (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to identify the implementation of HOTS in increasing the understanding and application of religious values ??through P5 activities in the school environment and its influence on students’ problem solving abilities. The importance of developing high-level thinking skills in learning and assessment in the field of Islamic religious education (PAI) because it has a central role in forming a deep understanding related to religious concepts. This research uses a qualitative approach with a case study method. Data collection using interviews, observation and documentation. Data analysis using Miels and Hubarman analysis techniques. Validity of research data with poleulation and increased research persistence. The research results are: first, the steps for implementing HOTS in PAI learning through P5 activities with structured planning and preparation, implementation, assessment and follow-up; second, the role of HOTS in PAI learning through P5 activities in improving students’ problem solving abilities, namely: improving students’ problem solving abilities, critical, analytical and creative thinking which are essential for solving complex problems, developing reflective and metacognitive attitudes; third, evaluation of the application of HOTS in PAI learning through P5 activities in improving students’ problem solving abilities through observations, interviews and questionnaires which provide a comprehensive picture of the effectiveness of the approach.